Financial System Of Village Fund Management Accountability - Kaharuddin (Journal of Management, 2023)
The purpose of this study is to ascertain how the internal control system and the village financial system in the districts of Beloro and Kutai Kartanegara affect the accountability of village fund management. A total of 105 respondents, including village chiefs, village secretaries, hamlet heads, BPD, youth leaders, and community leaders, participated in this study. In this study, the AMOS 24.0 model and descriptive analysis were employed. In this quantitative study, primary data from observations, interviews, questionnaires, and photos are combined. The study's findings indicate that the internal control system of the government and the village financial system both significantly and favorably affect the accountability of village financial management in all of the villages in Kutai Kartanegara Regency's Beloro District.